Pemeriksaan Penyakit Asam Urat Pada Karyawan Laboratorium Thamrin Berdasarkan Usia - Rani Eka Sapitri; Jamilah Nasution; Ida Fauziah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2022)
Gout is a disease caused by the buildup of purines that form purine crystals in the joints which causes pain in the joints. This study aims to determine the relationship between age and uric acid levels in employees at the Thamrin Medan Clinical Laboratory. This study uses a descriptive method with correlation analysis test, using a total sampling technique with a total of 56 respondent, with a male gender group of 14 people and a female gender group of 42 people. The result of the correlation test with a significance level 1 = negative correlation and ≥ 1 = positive correlation and the results obtained from n = 56 people with a value of r = 0,389602 with information (0.20-0.399= low correlation), meaning that there is no significant relationship between age and uric acid levels in Thamrin Medan Clinical Laboratory Employees.